Kreativitas Digital dalam Media Pembelajaran Sosial-Emosional Anak Dini - Alivia, Revina; Kasandra, Revalina; Widyasari, Choiriyah Widyasari (Universitas Muhammadiyah Surakarta, 2024)
Social-emotional development is an important aspect in shaping young children's personality and interaction skills. In the digital era, technology-based media such as educational apps, animated videos and interactive games offer new opportunities to support children's social-emotional development. This research aims to analyze the role of digital creativity in early childhood social-emotional learning media and explore the challenges and solutions that can be applied to maximize the benefits of digital media. Using a qualitative descriptive method through a review of current literature, this study found that well-designed digital media can help children improve empathy, emotion management and communication skills. However, challenges such as the risk of exposure to inappropriate content and screen addiction require a collaborative approach between parents, educators and app developers. A blended learning approach is an effective solution by integrating digital learning experiences and in-person interactions. With wise supervision and appropriate content design, digital creativity can be an innovative tool in creating holistic learning that supports early childhood social-emotional development.